The after crisis government-driven credit expansion in Brazil: A firm level analysis. (July 2015) - Bonomo, Marco; Brito, Ricardo D.; Martins, Bruno
Abstract: Government-driven credit had an important role in countervailing the private credit crunch in Brazil during the recent financial crisis. However, government credit concessions continued to expand after the economy recovered. This paper investigates some important features of this expansion using a huge repository of loan contracts between banks and firms, composing an unbalanced panel of almost 1 million firms between 2004 and 2012. Our results show that larger, older and less risky firms have benefited most from the government sponsored credit expansion. Additionally, although a higher access to earmarked credit tends to lead to higher leverage, the effect on investment appears to be insignificant for publicly traded firms. Since interest rates on earmarked loans are lower than market interest rates, firms with higher access to this type of loan tend to have lower cost of debt.